AN ANALYSIS OF DIRECT AND INDIRECT SPEECH ACTS PERFORMED BY MAIN CHARACTER IN THE MOVIE REVENANT SCRIPT - Fyngky Oktadistio; Mazrul Aziz; Zahrida . (Journal of English Education and Teaching, 2018)
This Research Entitled “An Analysis Of Direct And Indirect Speech Acts Performed By Main Character In The Movie Revenant Script”. This research was a descriptive analysis that discusses direct and indirect speech acts in movie script entitled ‘The Revenant.’ In analyzing the script, there was used theory by Yule (1996).The data in this research based on main characters’ utterances. The purpose of this analysis was to find out the types, and functions of speech act whether it is direct speech act or indirect speech act in the movie script entitled ‘The Revenant.’ From the analysis, it was found that both direct speech acts and indirect speech acts are used by main characters in this movie. The most dominant type of speech act used in the movie script was direct speech act (13 utterances) and then followed by indirect speech act (9 utterances). The direct speech act was classified again into declarative type (2 utterances) imperative type (5 utterances) and interrogative type (6 utterances). Indirect speech acts were also classified again into declarative type (8 utterances) and Interrogative (1 utterance). For the functions, direct speech acts are classified into the statement (2 utterances), order/request (5 utterances), and the last function of the question (6 utterances). Indirect speech act also classified into question (9 utterances), and no functions of statement and order. Based on the result, the researcher found that Felicity Conditions and genre were the factors affected main characters in producing direct speech acts more than indirect speech acts.